Genetic Diversity of HLA Class I and Class II Alleles in Thai Populations: Contribution to Genotype-Guided Therapeutics - Patompong Satapornpong; Patompong Satapornpong; Patompong Satapornpong; Pimonpan Jinda; Pimonpan Jinda; Thawinee Jantararoungtong; Thawinee Jantararoungtong; Napatrupron Koomdee; Napatrupron Koomdee; Chonlawat Chaichan; Chonlawat Chaichan; Jirawat Pratoomwun; et al. (Frontiers Media S.A., 2020)
Human leukocyte antigen (HLA) class I and II are known to have association with severe cutaneous adverse reactions (SCARs) when exposing to certain drug treatment. Due to genetic differences at population level, drug hypersensitivity reactions are varied, and thus common pharmacogenetics markers for one country might be different from another country, for instance, HLA-A*31:01 is associated with carbamazepine (CBZ)-induced SCARs in European and Japanese while HLA-B*15:02 is associated with CBZ-induced Stevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) among Taiwanese and Southeast Asian. Such differences pose a major challenge to prevent drug hypersensitivity when pharmacogenetics cannot be ubiquitously and efficiently translated into clinic. Therefore, a population-wide study of the distribution of HLA-pharmacogenetics markers is needed. This work presents a study of Thai HLA alleles on both HLA class I and II genes from 470 unrelated Thai individuals by means of polymerase chain reaction sequence-specific oligonucleotide (PCR-SSO) in which oligonucleotide probes along the stretches of HLA-A, -B, -C, -DRB1, -DQA1, and -DQB1 genes were genotyped. These 470 individuals were selected according to their regional locations, which were from North, Northeast, South, Central, and a capital city, Bangkok. Top ranked HLA alleles in Thai population include HLA-A*11:01 (26.06%), -B*46:01 (14.04%), -C* 01:02 (17.13%), -DRB1*12:02 (15.32%), -DQA1*01:01 (24.89%), and -DQB1*05:02 (21.28%). The results revealed that the distribution of HLA-pharmacogenetics alleles from the South had more HLA-B75 family that a typical HLA-B*15:02 pharmacogenetics test for SJS/TEN screening would not cover. Besides the view across the nation, when compared HLA alleles from Thai population with HLA alleles from both European and Asian countries, the distribution landscape of HLA-associated drug hypersensitivity across many countries could be observed. Consequently, this pharmacogenetics database offers a comprehensive view of pharmacogenetics marker distribution in Thailand that could be used as a reference for other Southeast Asian countries to validate the feasibility of their future pharmacogenetics deployment.